Analisis Perhitungan Biaya Produksi menggunakan Metode Variable Costing pada Meubel Budi Karya - Dewi, Diyah Persilliana; Hayati, Sari (Universitas Darwan Ali, 2020)
Production costs are the accumulation of all costs needed in the production process to produce a product or goods. Production costs consist of Raw Material Costs, Direct Labor Costs, and Factory Overhead Costs. This study aims to find out the Production Cost Calculation Using Variable Costing Methods at BUDI KARYA Furniture. This type of research is quantitative descriptive research using primary data and secondary data in December 2018 obtained from the company. The results of this study indicate that the calculation of production costs for Raw Material Costs is Rp. 6,375,000, Direct Labor Costs of Rp. 7,100,000, and Factory Overhead Cost of Rp. 1,870,000. For the calculation of Profit and Loss during December 2018 Meubel Budi Karya received a business net profit of Rp. 21,973,000.